A 245 GHz transmitter in SiGe technology - Schmalz, Klaus; Borngräber, Johannes; Heinemann, Bernd; Rücker, Holger; Scheytt, Christoph (Radio Frequency Integrated Circuits Symposium (RFIC), 2012 IEEE)
A 245 GHz transmitter for sensing applications has been realized, which consists of a push-push VCO with 1/64 frequency divider, a transformer- coupled one-stage power amplifier, and a frequency doubler. It is fabricated in 0.13μm SiGe:C BiCMOS technology with f T /f max of 300GHz/500GHz. The peak output power of the transmitter is 2 dBm. The 3-dB bandwidth reaches from 229 GHz to 251 GHz. The output power is 1 dBm at 245 GHz. The transmitter dissipates 0.29 W. Additionally, a test-circuit with an integrated two-stage power amplifier and a frequency doubler is presented, which reaches 1.4 dBm at 245 GHz and dissipates 0.19 W.

An integrated 125GHz Sensor with read-out circuit for permittivity measurement of liquids - Laemmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
In this publication an integrated dielectric sensor with read-out circuit in SiGe BiCMOS technology at 125GHz is presented. The sensor consist of a 500 µm shorted half-wave coplanar waveguide transmission line in the top metal layer. Read-out of the sensor is performed by measurement of its reflection coefficient with an integrated multiprobe reflectometer and signal source. The MMIC has been fabricated in a 190-GHz f T SiGe:C BiCMOS technology and assembled on a printed circuit board. Functionality of the sensor is demonstrated with a stimulus frequency from 118 to 133GHz with immersion of the sensor into a binary methanol-ethanol mixture.

A fully digital polar modulator for switch mode RF power amplifier - Ostrovskyy, Philip; Scheytt, Christoph; Lee, SungJun; Park, BongHyuk; Jung, JaeHo (Proc. IEEE Int Circuits and Systems (ISCAS) Symp)
In this paper, a novel fully digital modulator for a switch mode power amplifier (SMPA) is presented. The modulator converts the input baseband amplitude and phase signals into a two-level pulse train for driving an RF SMPA. The simulation results demonstrated a proof of the concept. The proposed architecture is analyzed in terms of accuracy by measuring EVM. The impact of the modulator parameters on the SMPA performance is investigated and corresponding results are shown. The modulator was simulated with a 20 MHz LTE signal.

Vertical Graphene Base Transistor - Mehr, Wolfgang; Dabrowski, Jarek; Lemme, Max C.; Lippert, Gunther; Lupina, Grzegorz; Ostling, Mikael; Xie, Ya-Hong; Scheytt, Christoph ((Refa) FB/IE Zeitschrift für Unternehmensentwicklung und Industrial Engineering)
We present a novel graphene-based-device concept for a high-frequency operation: a hot-electron graphene base transistor (GBT). Simulations show that GBTs have high current on/off ratios and high current gain. Simulations and small-signal models indicate that it potentially allows terahertz operation. Based on energy-band considerations, we propose a specific material solution that is compatible with SiGe process lines.

60 GHz Polarimetric MIMO Sensing: architectures and technology - Garcia-Ariza, Alexis-Paolo; Müller, Robert; Stephan, Ralf; Wollenschläger, Frank; Schulz, Alexander; Elkhouly, Mohamed; Scheytt, Christoph; Trautwein, Uwe; Müller, Jens; Thomae, Reiner; Hein, Matthias (EuCAP2012 (European Conference on Antennas and Propagation))
Millimeter-Wave (mm-W) is considered a potential technology for high-data rate wireless transmission and for high-resolution short-range radar, due to the 7-9 GHz bandwidth at the 60 GHz unlicensed band available worldwide. Developing ultrawideband architectures including multiple-input-multiple-output (MIMO) antenna systems at mm-W offer many advantages including jointly optimized analogue and digital signal processing at carrier frequency and baseband. This allows for flexible antenna designs and reduced losses, as many passive structures can be avoided at both sides of the link. Besides, based on flexible polarimetric approaches, the polarimetric propagation of electromagnetic waves can be exploited. In this paper we present a 60 GHz polarimetric MIMO system architecture, which includes analogue miniaturized frontends designed and manufactured by multi-layer packaging technologies. Such architecture permitted the design of compact MIMO radar and multi-dimensional channel sounding. The MIMO approach allows not only polarimetric filtering and fully polarimetric/directional signal processing to increase the signal-to-clutter-plus-noise ratio of mm-W radar systems, but also the full characterization of wireless channels including multipath with orthogonal polarizations.

120 GHz phased-array circuits in 0.25 µm SiGe BiCMOS technology - Elkhouly, Mohamed; Glisic, Srdjan; Ellinger, Frank; Scheytt, Christoph (GeMIC 2012)
This paper describes the design of D-band phased-array circuits in 0.25 μm technology. The first part describes the design of the passive components which are used in the phased-array systems such as balun, Wilkinson divider and branch-line coupler. A millimeter-wave vector-modulator is designed to support both amplitude and phase control for beam-forming applications. In the second part the designed circuits are integrated together to form a two channel 110-130 GHz phased-array chip. Each channel exhibits 360° phase control with 15 dB of amplitude control range and gain of -10 dB. The entire chip draws 45 mA from 3.3 V supply. The millimeter-wave phase shifting and the low-power consumption makes it ideal for highly integrated scalable beam-forming systems for both imaging and communication.

A 200mV 32b Subthreshold Processor with Adaptive Supply Voltage Control - Luetkemeier, Sven; Jungeblut, Thorsten; Porrmann, Mario; Rückert, Ulrich (Proc. IEEE Int. Solid-State Circuits Conf. Digest of Technical Papers)
In recent years, subthreshold operation has become a research focus for digital systems with limited energy budget (e.g. mobile, battery-powered devices, radio frequency identification (RFID), wireless sensor networks, or biomedical applications). Subthreshold operation allows for such low power consumption by reducing the supply voltage of the circuit below the threshold voltage of the transistors. As dynamic power depends quadratically on supply voltage, and static power depends exponentially on supply voltage, considerable power savings are achieved. At the same time propagation delays increase due to reduced transistor currents. Effectively, energy consumption per cycle can typically be reduced by a factor of 10 using subthreshold operation.

A 245 GHz CB LNA and SHM mixer in SiGe technology - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (SiRF 2012 (Silicon Monolithic Integrated Circuits in RF Systems))
The paper presents a four stage 245 GHz LNA in an f t /f max =280/425 GHz SiGe technology and a 4 th sub harmonic 245 GHz transconductance mixer in an f t /f max =250/300 GHz SiGe technology. The LNA takes advantage of common base (CB) topology for each stage and has 12 dB gain at 245 GHz, while exhibiting a 3 dB bandwidth of 26 GHz. It has a supply voltage of 2V and power dissipation of 28 mW. The transconductance mixer has -7 dB conversion gain at 245 GHz with an LO power of 8 dBm at 61 GHz. The mixer draws 9.8 mA at 3V. Simulation results of the receiver comprising the CB LNA and SHM mixer are given.

A 62GHz Reflectometer for Biomedical Sensor Readout in SiGe BiCMOS Technology - Laemmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (SiRF 2012 (Silicon Monolithic Integrated Circuits in RF Systems))
In this publication an integrated reflectometer in SiGe BiCMOS technology for sensor readout at 62 GHz is presented. The circuit includes an oscillator, a six-port reflectometer, and a dummy sensor for verification purposes. The circuit has a bandwidth of 8GHz at a center frequency of 62 GHz. It operates at 3.75V supply voltage and consumes 282 mW. The measurement principle is demonstrated and the scattering parameters of the dummy sensor are compared to measurement of a breakout circuit with a commercially available vector network analyzer. The circuit has been fabricated in a 190-GHz SiGe:C BiCMOS technology and occupies an area of 0.9 mm 2 .

122 GHz Radartransceiver und Komponenten in 0.13ym SiGe BiCMOS - Scheytt, Christoph; Debski, Wojciech; Sun, Yaoming; Wang, Ruoyu; Winkler, Wolfgang

Local Navigation Strategies for Multi-Robot Exploration - Tanoto, Andry; Rückert, Ulrich (From Simulation to Experimentation with Mini-Robots)
This paper presents two local navigation strategies for multi-robot systems in performing exploration of unknown environments. The strategies are based on the frontier cell for mapping the environment and navigating in it. Additionally, two coordination strategies are used to solve possible conflicts among robots. Key criteria investigated are the efficiency and effectiveness represented by the completion time, traveled distance, the total steps, and the task distribution. The developed algorithms are tested in simulations as well as in experiments with Khepera III mini robots running on the Teleworkbench. To evaluate the robustness of the developed algorithms, tests are performed under different environmental configurations and varying numbers of robots. The results show the advantages of both proposed strategies in different situations such as environment types and starting positions.

Multi-Robot System Validation: From Simulation to Prototyping with Mini Robots in the Teleworkbench - Tanoto, Andry; Werner, Felix; Rückert, Ulrich; Sitte, Joaquin (Advances in Autonomous Mini Robots)
One challenging aspect in the development of multi-robot systems is their validation in a real environment. However, experiments with real robots are considerably tedious as experimenting is repetitive and consists of several steps: setup, execution, data logging, monitoring, and analysis. Moreover, experiments also require many resources especially in the case when involving many robots. This paper describes the role of the Teleworkbench as a platform for conducting experiments involving mini robots. The Teleworkbench offers functionality that can help users in validating their robot software from simulation to prototyping using mini robots. A traffic management system is used as a scenario for demonstrating the support of the Teleworkbench for validating multi-robot systems.

Mixed-Signal PSSS-Empfänger - Scheytt, Christoph
PSSS-Dekodierschaltung, dadurch gekennzeichnet, dass das analoge PSSS-Eingangssignal mit N Spreizsequenzen und N Verknüpfungselementen (z. B. Multiplizierer) verknüpft werden und die Ausgangssignale der N Verknüpfungselemente mit N analogen Integrierern auf integriert werden, dass die Integrierer jeweils zum Beginn der empfangenen Spreizsequenzen gleichzeitig mit dem Signal SYNC zurückgesetzt werden, dass der Integrator über die Dauer einer Code-Sequenz das Eingangssignal auf integriert, dass nach der Integration an den Ausgängen der Integratoren jeweils das dekodierte Datensignal anliegt, dass die Ausgangssignale der Integrierer mit N parallelen einem AD-Wandler digitalisiert werden.

mm-Wave SOC and SIP Design for 122 GHz Radar SSensor in the EU-FP7 Project SUCCESS - Sun, Yaoming; Beer, Stefan; Scheytt, Christoph; Wang, Ruoyu; Zwick, Thomas (RF-MST Cluster Workshop on MEMSWAVE 2012)

40 Gb/s VCSEL driver IC with a new output current and pre-emphasis adjustment method - Sedighi, Behnam; Scheytt, Christoph (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
Design of a 40 Gb/s VCSEL driver IC capable of providing up to 10mA current to common-cathode VCSELs is presented. Using low-power bandwidth enhancement techniques, a prototype IC is successfully developed in 180-GHz SiGe BiCMOS technology. Measured results show 34 GHz of bandwidth, open eye diagram with rise/fall time below 10 ps, and power dissipation of 130 mW.

Low-power BiCMOS track-and-hold circuit with reduced signal feedthrough - Sedighi, Behnam; Borokhovych, Yevgen; Gustat, Hans; Scheytt, Christoph (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
this paper presents a new circuit for high-speed BiCMOS track-and-holds. The proposed approach improves the signal feedthrough in the hold mode and the bandwidth in the tracking mode. A prototype circuit is implemented in a 0.13 µm BiCMOS technology, operating at 10 GS/s and consuming 19 mW from 3.3 V supply. It is shown that the circuit is capable of providing a harmonic distortion below −50 dB.

Low-power 20-Gb/s SiGe BiCMOS driver with 2.5 V output swing - Sedighi, Behnam; Ostrovskyy, Philip; Scheytt, Christoph; Stille, Karl Stephan Christian; Böcker, Joachim (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
this paper investigates low-power design of high-speed and high-swing electronic driver circuits. A method to estimate and optimize the power consumption of such driver ICs is presented. A 20-Gb/s driver circuit is fabricated in 0.25 µm SiGe BiCMOS process and an output swing of 2.5 V pp is measured. The driver consumes 0.75 W from 5 V supply.

Automated Source Code Annotation for Timing Analysis of Embedded Software - Joy, M. tech. Mabel Mary; Becker, Markus; Mathews, Emi; Müller, Wolfgang (In Proceedings of Advanced Computing and Communications Conference 2012 (ADCOM 2012))

Real-Time Android: Deterministic Ease of Use - Mauerer, Wolfgang; Hillier, Gernot; Sawallisch, Jan; Hönick, Stefan; Oberthür, Simon (Proceedings of Embedded Linux Conference Europe, 5. - 7. Nov. 2012)

Biologically Inspired Swarm Robotic Network Ensuring Coverage and Connectivity - Mathews, Emi; Graf, Tobias; Kulathunga, K. S. S. B. (In Proceedings of IEEE International Conference on Systems, Man, and Cybernetics (SMC 2012))